The symmetry indices of malar mounds for zygomatic bone fracture management based on a computed tomographic model. Issue 7 (1st July 2021) - Wang, Tien-Hsiang; Yu, Wen-Chan; Chen, Zih-Hua; Tien, Yao-Hsuan; Chen, Wei-Ming; Chiu, Fang-Yau; Wang, Shyh-Jen
Abstract : Background: To date, plastic surgeons do not have an objective method of measuring facial symmetry for zygomatic bone fracture management. Based on clinical practice, the authors utilized a 3-dimensional (3D) model to propose the symmetry index from the anterior view (SIAV) and the symmetry index from inferior view (SIIV). This study aimed to assess the application of these 2 indices. Methods: The SIAV is defined as the distance between the superior and lower orbital rims (DSLOR) of the defective side divided by that of the healthy side in the anterior view. The SIIV is defined as the area within the region of interest (AROI) of the defective side divided by that of the healthy side in the inferior view. We retrospectively reviewed 95 patients who underwent zygomatic fracture surgery at our medical center from January 2017 to September 2020. The Patients who had bilateral zygomatic fractures and did not have both pre- and postoperative computed tomography (CT) images were excluded. Results: Five out of the 95 patients were enrolled in this study. The difference between pre- and postoperative mean AROI and DSLOR on the healthy side was not significant. The insignificant difference indicates the repeatability of the measurement of the 3D skull model and different CT machines would not affect the calculation of AROI and DSLOR. The mean values of postoperative SIAV (1.06 ± 0.07) and SIIV (1.02 ± 0.08) were closer to 1 than the preoperative values (0.97 ± 0.09 and 1.10 ± 0.12). Although the difference was not statistically significant, the SIIV and SIAV would numerically present the changes in malar bone fracture postoperatively. Conclusion: The SIAV and SIIV based on clinical practice could numerically assess the symmetry of the malar mound.